New genus of Cladocera of subfamily Aloninae (Anomopoda: Chydoridae) from the Mekong River - Sinev, Artem Y.; Tiang-Nga, Supatra; Sanoamuang, La-Orsri (Zootaxa, 2017)
A rheophylous cladoceran, Rheoalona mekongensis sp. nov., gen. nov. (Anomopoda: Chydoridae: Aloninae) is described from the Mekong River, South-East Asia. Rheoalona gen. nov. belongs to the Coronatella-branch of Aloninae, it differs from Karualona Dumont & Silva-Briano, 2000 in absence of seta 1 of IDL of thoracic limb I and by particularly strong lateral setae of postabdomen; from Anthalona Van Damme, Sinev & Dumont, 2011 in a wide connection between major head pores, lack of cosmaria, and two-flaming torch setae of limb IV; and from Coronatella Dybowski & Grochowski, 1894 in two major head pores, very small elementary denticles of postabdomen, and a very small basal spine of postabdominal claw. R. mekongensis sp. nov. is specially adapted for dwelling in the upper layer of fine sediments of turbid rivers. Our finding stress the importance of sampling in riverine habitats for the full inventories of the cladoceran fauna.